Antimicrobial resistance of bacterial agents of the upper respiratory tract in south Indian population - K Kousalya; S Thirumurugu; D C Arumainayagam; R Manavalan; J Vasantha; C. Uma Maheswara Reddy (Wolters Kluwer Medknow Publications, 2010)
The study was aimed at determining bacterial agents of the upper respiratory tract and the susceptibility patterns of isolates to antibiotics. The throat swab samples from 250 patients suspected of upper respiratory tract infection (URTI) were obtained from the General Medicine outpatient department of a Rural Health Centre of Rajah Muthiah Medical College and Hospital (RMMC and H), Annamalai University, Chidambaram, Tamilnadu, India and inoculated in the culture medium. The bacterial infection was confirmed only in 228 patients. The organisms isolated on medium were identified by their cultural, morphological and biochemical characteristics. StaphzIocccus aureus was identified as the most prevalent bacterial isolate (45.61%) followed by β hemolytic streptococci (22.51%). Thirty four strains (14.91%) were identified as Klebsiella penumoniae, 19 (8.33%) as Pseudomonas aeruginosa and the rest belonged to a hemolytic streptococci, Escherichia coli and Haemophitus influenzae. All Staphylococcus spp, were resistant to penicillin., ampicillin and co-trimoxazole. All the isolates were resistant to at least one antibiotic. The overall resistance rates were generally low for gentaruicin, cefixine and ceftazidime respectively.